ALTERATIONS OF LIPID PROFILE LEVELS IN 7,12-DIMETHYLBENZ(A)ANTHRACENE INDUCED ULCERATIVE COLITIS RAT MODEL - P, Geetha; B, Lakshman Kumar; U, Indra; B, Pavithra Sheetal (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: Ulcerative colitis is a type of inflammatory bowel disease is a chronic gastrointestinal disorder characterized by intestinal inflammation and mucosal tissue damage. We examined the lipid profile levels in murine model of 7,12 Dimethylbenz(a)anthracene induced ulcerative colitis. Methods: Serum was separated from whole blood and was used to determine the lipid profile such as total cholesterol (TC), phospholipids (PL), triglycerides (TG), free fatty acids, high density lipoprotein (HDL-C) and low density lipoprotein (HDL-C). Results: Ulcerative colitis rats exhibit low level of low density lipoprotein cholesterol and total cholesterol. No significant difference was observed in high density lipoprotein and triglycerides and significant difference was observed in phospholipids and free fatty acid serum levels. This communication highlights the lipid profile that occurs in ulcerative colitis. Conclusion: This study, thus, provides valuable information about the disturbances in the lipids and lipoproteins occur in ulcerative colitis. Keywords: Ulcerative colitis, 7,12-Dimethylbenz(a)anthracene, Lipoprotein, Low-density lipoprotein, Phospholipids.